A Lab‐On‐chip Tool for Rapid, Quantitative, and Stage‐selective Diagnosis of Malaria. Issue 14 (13th May 2021) - Giacometti, Marco; Milesi, Francesca; Coppadoro, Pietro Lorenzo; Rizzo, Alberto; Fagiani, Federico; Rinaldi, Christian; Cantoni, Matteo; Petti, Daniela; Albisetti, Edoardo; Sampietro, Marco; Ciardo, Mariagrazia; Siciliano, Giulia; et al.
Abstract: Malaria remains the most important mosquito‐borne infectious disease worldwide, with 229 million new cases and 409.000 deaths in 2019. The infection is caused by a protozoan parasite which attacks red blood cells by feeding on hemoglobin and transforming it into hemozoin. Despite the WHO recommendation of prompt malaria diagnosis, the quality of microscopy‐based diagnosis is frequently inadequate while rapid diagnostic tests based on antigens are not quantitative and still affected by non‐negligible false negative/positive results. PCR‐based methods are highly performant but still not widely used in endemic areas. Here, a diagnostic tool (TMek), based on the paramagnetic properties of hemozoin nanocrystals in infected red blood cells (i‐RBCs), is reported on. Exploiting the competition between gravity and magnetic forces, i‐RBCs in a whole blood specimen are sorted and electrically detected in a microchip. The amplitude and time evolution of the electrical signal allow for the quantification of i‐RBCs (in the range 10–10 5 i‐RBC µL −1 ) and the distinction of the infection stage. A preliminary validation study on 75 patients with clinical suspect of malaria shows on‐field operability, without false negative and a few false positive results. These findings indicate the potential of TMek as a quantitative, stage‐selective, rapid test for malaria. Abstract : Malaria is caused by the Plasmodium parasite which feeds on hemoglobin and produces paramagnetic hemozoin crystals within red blood cells (RBCs). A quantitative and stage‐selective pan‐malaria diagnostic test is disclosed, based on a simple concept implemented on a microchip: the sorting and electrical detection of infected RBCs, thanks to the competition between magnetic and gravity forces.